Considerations on the Best Interests of the Child as a Principle of Exercising Parental Authority - BOBAR, Cosmina Flavia (Journal of Legal Studies, 2018)
The principle of the best interests of the child is the basis for international or national normative documents adopted after the 1989 UN Convention on the Rights of the Child. They enshrine the prevalence of this principle in any decision that must be made with regard to the child, and regardless of its author. In the matter of parental authority, the Romanian Civil Code subordinates parental rights and duties to this principle, placing the interests of the child above the interests of parents. This study presents such aspects as referring to the principle of the best interests of the child, including from a historical perspective, while also emphasising concern in the doctrine for defining but also establishing criteria to appraise the best interests of the child, prior to the amendment of Law no. 272/2004 on the protection and promotion of children's rights.